Untitled - (:unkn) unknown (Ocean Comfort Company m. b. H., Bremen, 2008)
Photo of an East Indian Female in traditional wear and jewellery. includes postage but illegible.
Colour:Browm and White ; Style:Portrait ; Other:Bordered, Divided
Keywords: Postcards; Women, East Indian; 1926